2012
DOI: 10.1029/2012wr011965
|View full text |Cite
|
Sign up to set email alerts
|

A new model for the spectral induced polarization signature of bacterial growth in porous media

Abstract: [1] The complex conductivity of porous materials and colloidal suspensions comprises two components: an in-phase conductivity associated with electromigration of the charge carriers and a quadrature conductivity associated with the reversible storage of the charges at some polarization length scales. We developed a quantitative model to investigate the frequency domain induced polarization response of suspensions of bacteria and bacteria growth in porous media. Induced polarization of bacteria (a polarization)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
65
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(76 citation statements)
references
References 64 publications
10
65
0
1
Order By: Relevance
“…The low-frequency polarization of bacteria in porous media has been recently modeled by Revil et al (2012a) with a special emphasis on Gram-positive bacteria. Revil et al (2012a) use a polarization model of the double layer surrounding the bacterial cells. They upscaled their results to a representative elementary volume of a porous material with a composite model taking into account the presence of the bacteria and the grains.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The low-frequency polarization of bacteria in porous media has been recently modeled by Revil et al (2012a) with a special emphasis on Gram-positive bacteria. Revil et al (2012a) use a polarization model of the double layer surrounding the bacterial cells. They upscaled their results to a representative elementary volume of a porous material with a composite model taking into account the presence of the bacteria and the grains.…”
Section: Introductionmentioning
confidence: 99%
“…The in-phase component of the complex conductivity describes the electromigration of the charge carriers in the material, whereas its quadrature component describes the polarization. The induced polarization method has been qualitatively shown to be sensitive to the presence of bacteria in porous media (Abdel Aal et al, 2004Ntarlagiannis et al, 2005a;Davis et al, 2006;Albrecht et al, 2011;Revil et al, 2012a;Zhang et al, 2012). The low-frequency polarization of bacteria in porous media has been recently modeled by Revil et al (2012a) with a special emphasis on Gram-positive bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…As in Weller et al (2006) and Revil et al (2012b), a considerable variation in the spectra of conductivity amplitude and phase shift can be observed in laboratory investigations of peat, wood and soil samples. Weller et al (2006) concluded that characteristic features of phase spectra can be used to detect wooden relics of trackways or pile dwelling from laboratory investigations.…”
Section: Discussionmentioning
confidence: 96%
“…Weller et al (2006) concluded that characteristic features of phase spectra can be used to detect wooden relics of trackways or pile dwelling from laboratory investigations. Revil et al (2012b) developed a quantitative model to investigate the frequency domain induced polarization response of suspensions of bacteria and bacteria growth in porous media. They showed that the induced polarization of bacteria (α polarization) is related to the properties of the electrical double layer of the bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation